Pengaruh moderate intensity continuous exercise (MICE) dalam perbaikan kognitif lansia - Raminda, Santri; Ni'mah, Anisah Khanin; Aliyun, Fatimah Wahab; Kurniawan, Ryanda Masri; Ramadhani, Andina Risky; Nugroho, Rafi Agusti; Zahirah, Fidela Kaila Reva (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2024)
Background: Cognitive in the elderly is the ability to think, remember, learn, and verbal ability. Cognitive function is a mental process that includes attention, perception, and knowledge. Cognitive impairment in the elderly is a health problem that occurs more frequently with age. Cognitive impairment can affect various aspects of mental function and thinking ability in the elderly. Cognitive impairment in the elderly cannot be cured, but it can be prevented and overcome. Purpose: To see the effect of moderate continuous intensity exercise (MICE) on cognition in the elderly with anaerobic fitness levels. Method: Quasi-experimental study with pre-test and post-test two group design. The sample of this study was 20 elderly patients at the Bandar Lampung Health Center who became participants. Participants were divided into two groups, namely 10 participants in the intervention group and 10 participants in the control group. The intervention group was given MICE such as anaerobic gymnastics exercises while the control group was given a book to read for 30 minutes with the same time. Cognitive function is measured using the Montreal Cognitive Assessment Indonesia (MoCa – Ina) which consists of 30 points that will be tested by assessing several cognitive matrices: executive function, visuospatial, language, delayed recall, attention, abstraction and orientation for 10 minutes with a total score of 26 or more considered normal. Results: Based on the Shapiro Wilk test analysis in the normality test for the intervention group, the mean pre-test to post-test value was 23.70-26.70 with pValue = 0.15 and for the control group, the mean pre-test to post-test value was 25.30-27.20 with pValue = 0.44. Meanwhile, based on the paired sample test analysis in the cognitive influence test for the intervention group, the mean value was 3,000 with a standard deviation of 0.943 and pValue = 0.000, while for the control group, the mean value was 1,900 with a standard deviation of 1,370 and pValue = 0.002. Conclusion: Anaerobic fitness therapy can affect moderate continuous intensity exercise (MICE) on the cognitive abilities of the elderly. Elderly people with stable and good fitness intensity will benefit from reducing cognitive impairment. Suggestion: Elderly people should consider their fitness level individually as a therapeutic measure such as following the right exercise routine in an effort to improve cognitive abilities. Keywords: Anaerobic; Cognitive improvement; Elderly; Moderate continuous intensity exercise (MICE) Pendahuluan: Kognitif pada lansia adalah kemampuan berpikir, kemampuan mengingat, kemampuan belajar, dan kemampuan verbal. Fungsi kognitif merupakan proses mental yang meliputi perhatian, persepsi, dan pengetahuan. Gangguan kognitif pada lansia merupakan masalah kesehatan yang semakin sering terjadi dengan bertambahnya usia. Gangguan kognitif dapat memengaruhi berbagai aspek fungsi mental dan kemampuan berpikir lansia. Gangguan kognitif pada lansia tidak dapat disembuhkan, tetapi dapat dicegah dan diatasi. Tujuan: Untuk melihat efek moderate continuous intensity exercise (MICE) terhadap kognitif pada lansia dengan tingkat kebugaran anerobik. Metode: Penelitian quasi experimental dengan pre-test and post-test two group design. Sampel penelitian ini adalah 20 pasien lansia di Puskesmas Bandar Lampung yang menjadi partisipan. Partisipan dibagi menjadi dua kelompok yaitu 10 partisipan kelompok intervensi dan 10 partisipan kelompok kontrol. Kelompok intervensi diberikan MICE seperti latihan senam anaerobik sedangkan untuk kelompok control diberikan buku untuk dibaca selama 30 menit dengan waktu yang sama. Fungsi kognitif diukur menggunakan Montreal Cognitive Assessment Indonesia (MoCa – Ina) yang terdiri dari 30 point yang akan diujikan dengan menilai beberapa matrix kognitif: fungsi eksekutif, visuospasial, bahasa, delayed recall, atensi, abstraksi dan orientasi selama 10 menit dengan total skor 26 atau lebih dianggap normal. Hasil: Berdasarkan analisa shapiro wilk test dalam uji normalitas untuk kelompok intervensi mendapatkan nilai mean pre-test ke post-test sebesar 23.70-26.70 dengan pValue=0.15 dan untuk kelompok kontrol mendapatkan nilai mean pre-test ke post-test sebesar 25.30-27.20 dengan pValue=0.44. Sedangkan berdasarkan analisa uji paired sample test dalam uji pengaruh pada kognitif untuk kelompok intervensi mendapatkan nilai mean 3.000 dengan standar deviasi 0.943 dan pValue=0.000, sedangkan untuk kelompok kontrol mendapatkan nilai mean 1.900 dengan standar deviasi 1.370 dan pValue=0.002. Simpulan: Terapi kebugaran anaerobik dapat mempengaruhi moderate continuous intensity exercise (MICE) pada kognitif lansia. Lansia dengan intensitas kebugaran yang stabil dan baik akan memperoleh manfaat mengurangi gangguan kognitif. Saran: Lansia harus mempertimbangkan tingkat kebugaran secara individual sebagai tindakan terapi seperti mengikuti kegiatan rutinitas olahraga yang tepat dalam upaya memperbaiki kognitif.